2013
DOI: 10.1039/c3tc31385a
|View full text |Cite
|
Sign up to set email alerts
|

The influence of high magnetic field on electric-dipole emission spectra of Eu3+ in different single crystals

Abstract: In this work, the effect of pulsed high magnetic field on the integral intensity of the electric-dipole emission spectrum of Eu 3+ in YVO 4 :Eu 3+ and GdVO 4 :Eu 3+ single crystals was studied and the results showed magnetic field induced luminescence suppression in YVO 4 :Eu 3+ and luminescence expansion in GdVO 4 :Eu 3+ . The single crystals were prepared by the optical floating zone method. The strong effect of the magnetic field on the splitting and emission of 5 D 0 -7 F 2 and 5 D 0 -7 F 4 transitions in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 21 publications
1
31
0
Order By: Relevance
“…the Zeeman effect, tuning luminescence from lanthanide ions by an external magnetic field has been demonstrated in different systems. 24,25,31,32 In this paper, hexagonal NaYF 4 doped with an ion pair of Yb 3+ -Er 3+ is chosen to probe the magnetic field tuned UC luminescence. Likewise, the UC luminescence of lanthanide ions doped nanoparticles and phosphors also couples strongly with magnetic field as a result of the change in crystal local symmetry and intra-ion transitions of lanthanide ions.…”
mentioning
confidence: 99%
“…the Zeeman effect, tuning luminescence from lanthanide ions by an external magnetic field has been demonstrated in different systems. 24,25,31,32 In this paper, hexagonal NaYF 4 doped with an ion pair of Yb 3+ -Er 3+ is chosen to probe the magnetic field tuned UC luminescence. Likewise, the UC luminescence of lanthanide ions doped nanoparticles and phosphors also couples strongly with magnetic field as a result of the change in crystal local symmetry and intra-ion transitions of lanthanide ions.…”
mentioning
confidence: 99%
“…Du et al [85] observed the luminescence suppression in YVO 4 :Eu while a luminescence intensification in GdVO 4 :Eu single crystals for the two electric dipole transitions 5 D 0 → 7 F 2 and 5 D 0 → 7 F 4 of Eu 3+ . Du et al [85] observed the luminescence suppression in YVO 4 :Eu while a luminescence intensification in GdVO 4 :Eu single crystals for the two electric dipole transitions 5 D 0 → 7 F 2 and 5 D 0 → 7 F 4 of Eu 3+ .…”
Section: Controlling the Temperaturementioning
confidence: 99%
“…[ 3,4 ] Through codoping Dy 3+ and Eu 3+ ions into single phase R VO 4 materials, multicolor photoluminescence including white light can be easily realized. [ 5,6 ] With these outstanding properties plus the chemical and thermal stability, R VO 4 materials will be also given potential applications in the field of nanophosphors, optical polarizers, lithium ion batteries, birefringent and nuclear waste storage materials. [ 7–11 ]…”
Section: Introductionmentioning
confidence: 99%